(untitled) (Alberta Journal of Educational Research, 2011)
We report on international research that compares linguistic ecosystems, that is, socially constructed public attitudes and ideologies concerned with foreign-language (FL) learning, in Canada and Japan. Analyzing responses to three interview questions from 125 interviews with five categories of respondent in each country, we suggest that there are a number of key differences between the linguistic ecosystems of the two countries, most notably that whereas Canada appears to promote the learning of foreign culture with little support for FL learning, Japan appears to promote FL learning without the learning of foreign culture. Notre article porte sur la recherche internationale qui compare les écosystèmes linguistiques, c’est à dire les attitudes et idéologies publiques définies par la société et portant sur l’apprentissage d’une langue étrangère, du Canada à ceux du Japon. Une analyse des réponses à trois questions d’entrevue provenant de 125 entrevues avec cinq catégories de répondants de chaque pays nous porte à conclure qu’il existe quelques différences importantes entre les deux écosystèmes linguistiques des deux pays, notamment que le Canada semble promouvoir l’apprentissage d’une culture étrangère tout en fournissant peu d’appui pour l’apprentissage d’une langue étrangère, alors que le Japon semble promouvoir l’apprentissage d’une langue étrangère sans l’apprentissage d’une culture étrangère.